Middle ear biofilm and sudden deafness - a light and transmission electron microscopy study - Li, Hao; Staxäng, Karin; Ladak, Hanif M.; Agrawal, Sumit; Rask-Andersen, Helge (Frontiers in Neurology, 2024)
BackgroundThere still exists controversy about whether the healthy human middle ear mucosa is sterile or if it may harbor a diverse microbiome. Considering the delicacy of the human round window membrane (RWM), different mechanisms may exist for avoiding inner ear pathogen invasion causing sensorineural deafness. We re-analyzed archival human RWMs using light and transmission electron microscopy after decalcification to determine if bacteria are present in clinically normal human middle ears. We also searched for the presence of inborn immune defensive mechanisms within the round window niche (RWN), as previously reported in non-human primate ears.Materials and methodsFive round window niches, removed and directly fixed at transcochlear petroclival meningioma surgery, were re-investigated after ethical permission using light and transmission electron microscopy. The morphology of the RWM, including its bony attachment and pseudomembrane outline, was analyzed. Moreover, 64 human temporal bones were investigated using synchrotron phase-contrast imaging (SR-PCI) aiming to identify potentially “hidden” spaces, including the RWN potentially harboring infectious material.ResultsHistologic evidence of free-living bacteria and biofilm was found in 40% of RWNs in seemingly “healthy” middle ears. The RWM in these ears was pathologically changed with repealed epithelial and intercellular junctional integrity. Putative membranous defense machinery consisted of a lymphatic drainage system together with free phagocytic cells seemingly serving to protect the inner ear from alleged pathogens. Synchrotron analyses showed that a pseudomembrane was present in the human round window niche (RWN) in 80% of the specimens, of which 20% were complete. In 3%, the RWN contained dense tissue or serous fluid plugs partly obstructing the RWN. Infralabyrinthic clefts and tympanomeningeal fissures (Hyrtl’s fissure) were occasionally enclosed by delicate membranes near the round window. These may represent predilection sites for “hidden” infections potentially endangering inner ear function, particularly in connection with round window surgery.ConclusionConsidering the fragility of the normal human RWM, we speculate that occult colonies of biofilm may be a factor in surgeries involving the RWM, sensorineural hearing loss, and hearing preservation/fibrosis following cochlear implantation, and more controversially in hidden perilymph leaks causing sudden deafness and labyrinthine pathology.